Auditory brainstem response findings in a group of neurologically compromised children: a retrospective study - Baillieu, Karen Mary (My University, 2014)
There is a higher prevalence of hearing loss in children with diagnosed neurological disorders than the general paediatric population. It is therefore essential that these children have their hearing assessed. Conventional behavioural audiometry requires participation from the child, and in a majority of this population with neurological pathology this is not always possible owing to their neurocompromised state. These children will have to undergo objective testing, such as the Auditory Brainstem Response (ABR) in order to obtain estimated hearing thresholds, as this requires no active involvement from the patient. This study therefore aims to describe the audiological ABR findings in order to determine hearing function in this group and to establish a relationship between audiological ABR findings to behavioural audiometry findings where these exist in a group of neurologically disordered children in a tertiary hospital in South Africa. Methods: A retrospective review was conducted on 40 ABR patient records of children between the ages of 5 months and 10 years diagnosed with a neurological disorder. Behavioural audiometry results were then sought for these children, where these existed. Hearing status was described for each child per ear for both objective and behavioural results, and descriptive statistics were conducted. Results: 56.25 % (n=45) of ears in this study presented with normal hearing on ABR testing. No behavioural audiometry results were obtained in 72.5 % (n=58) of ears in this study. Results correlated between ABR and behavioural testing for only 7.5% (n=8) of ears tested and in all eight of these ears the hearing result was within normal hearing limits. Twelve and a half percent (n=10) of ears were misdiagnosed on behavioural testing. More premature infants were able to be tested behaviourally when compared to other pathologies. Cerebral palsy, Down’s Syndrome, prematurity and RVD were the pathologies in which the most hearing losses were diagnosed. Conclusions: Behavioural audiometry appears a largely unreliable method of hearing testing in children diagnosed with neurological disorders as results were obtained in only 27.5 % of the study sample; however it remains the gold standard in paediatric hearing testing in order to evaluate the entire auditory system and provides information on how a child processes sound, unlike ABR testing which only provides hearing information up to the auditory brainstem. This study highlights the high prevalence of hearing problems in children with neurological disorders and therefore the importance of hearing testing in this population. Hearing thresholds should be established for subsequent remediation via objective testing. Conditioning should continue simultaneously for a behavioural audiological test battery with adaptations for the child’s developmental ability.
Keywords: neurological disorder; hearing loss; ABR; behavioural audiometry